PERLINDUNGAN HUKUM TERHADAP HAK PENUMPANG DALAM INDUSTRI PENERBANGAN DI INDONESIA - NIM. A1012191143, MUHAMMAD LUQMAN (Jurnal Fatwa Hukum, 2025)
Abstract This research examines the legal protection of passenger rights in Indonesia's aviation industry, focusing on airlines' efforts to fulfill passenger rights and the government's role in regulation and oversight. Amid the rapid growth of the aviation industry, various issues such as delays, flight cancellations, and overbooking frequently disrupt passenger comfort and interests. Based on Law Number 1 of 2009 on Aviation and several international regulations, this study analyzes the fundamental rights passengers are entitled to and the legal protections available in Indonesia. This research employs a normative juridical approach by reviewing relevant legislation and case studies to assess the effectiveness of existing regulations in practice. The findings indicate that, although there are regulations guaranteeing passenger rights, the implementation of legal protections often faces obstacles, including discrepancies between regulations and field practices, weak law enforcement, and insufficient socialization of passenger rights. This study recommends the need for more consistent law enforcement, an enhanced government role in oversight, and efforts by airlines to improve service quality as part of their responsibility toward passengers. Keywords: legal protection, passenger rights, aviation industry, aviation regulations, Indonesia Abstrak Penelitian ini mengkaji perlindungan hukum terhadap hak penumpang dalam industri penerbangan di Indonesia, dengan fokus pada upaya pemenuhan hak penumpang oleh maskapai serta peran pemerintah dalam regulasi dan pengawasannya. Di tengah pesatnya perkembangan industri penerbangan, berbagai permasalahan seperti keterlambatan, pembatalan penerbangan, serta overbooking kerap kali mengganggu kenyamanan dan kepentingan penumpang. Berdasarkan Undang-Undang Nomor 1 Tahun 2009 tentang Penerbangan dan beberapa regulasi internasional, penelitian ini menganalisis hak-hak dasar yang seharusnya diterima oleh penumpang serta bentuk perlindungan hukum yang ada di Indonesia. Penelitian ini menggunakan pendekatan yuridis normatif dengan menelaah peraturan perundang-undangan terkait dan studi kasus yang relevan untuk menilai efektivitas regulasi yang ada dalam praktik. Hasil penelitian menunjukkan bahwa meskipun telah ada peraturan yang menjamin hak penumpang, implementasi perlindungan hukum sering kali menghadapi kendala, termasuk ketidaksesuaian antara regulasi dan praktik lapangan, lemahnya penegakan hukum, serta kurangnya sosialisasi hak-hak penumpang. Penelitian ini menyarankan perlunya penegakan hukum yang lebih konsisten, peningkatan peran pemerintah dalam pengawasan, serta upaya maskapai untuk meningkatkan kualitas layanan sebagai bagian dari tanggung jawab mereka terhadap penumpang. Kata Kunci: perlindungan hukum, hak penumpang, industri penerbangan, regulasi penerbangan, Indonesia